2017
DOI: 10.1001/jamacardio.2017.2945
|View full text |Cite
|
Sign up to set email alerts
|

Thermodilution vs Estimated Fick Cardiac Output Measurement in Clinical Practice

Abstract: There is only modest agreement between Td and eFick CI estimates. Thermodilution CI better predicts mortality and should be favored over eFick in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 34 publications
2
54
2
2
Order By: Relevance
“…Linear regression analysis showed only a modest correlation between TD and eFM among all three VO 2 estimation formulas. The coefficient of determination in the current study was higher than described in two other studies with a similarly sized cohort of patients affected by PH[17,21], as well as in a large retrospective study of all-comers[20] (S7 Table). CI as assessed by the formulas of LaF and Be resulted in higher values than CI-TD in patients with low CI-states.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…Linear regression analysis showed only a modest correlation between TD and eFM among all three VO 2 estimation formulas. The coefficient of determination in the current study was higher than described in two other studies with a similarly sized cohort of patients affected by PH[17,21], as well as in a large retrospective study of all-comers[20] (S7 Table). CI as assessed by the formulas of LaF and Be resulted in higher values than CI-TD in patients with low CI-states.…”
Section: Resultscontrasting
confidence: 60%
“…[2224] Similar trials comparing eFM and TD often did not report the formulas behind VO 2 calculations due to their retrospective design. [17,20] An extensive analysis comparing the eFM and TD-method suggested that age is a major contributor to differences between the two methods, but did not further investigate the relevance of this observation. [20] As sarcopenia is frequent among elderly patients, especially in heart failure, VO 2 assumptions based on young patient study-cohorts might be misleading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodynamic assessment involves measuring cardiac function through several parameters such as heart rate (HR), blood pressure (BP), stroke volume (SV) and cardiac output (CO). Hemodynamic monitoring primarily relies on the current gold standard—thermodilution (using pulmonary artery catheter (PAC)) [ 1 , 2 , 3 , 4 ]—which is an invasive method along with semi- or minimally invasive techniques employing Doppler echocardiography [ 5 , 6 , 7 , 8 , 9 ]. Due to concerns around patient comfort and continuous measurements, alternatives to the existing hemodynamic assessment methods have always been of interest [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A very recent retrospective study, in more than 12,000 patients who underwent right heart catheterization but were not necessarily hospitalized in ICU, found between thermodilution and an oxygen-uptake-based Fick method, an acceptable systematic bias of 0.4% but poor limits of agreement from −1.31 to +1.27 l/min; and a difference of more than 20% between measured CO in 40% of patients ( 45 ).…”
Section: Respiratory Derived Co Monitoring System: Partial Co mentioning
confidence: 99%